ELECTROCARDIOGRAM CHANGES IN PREHYPERTENSIVE SUBJECTS – EPIDEMIOLOGY OF HYPERTENSION IN CROATIA-1 (EH UH-1) STUDY. (June 2022) - Frkanec, Stjepan; Katic, Luka; Strbac, Tea; Trobonjaca, Adrian; Jelakovic, Ana; Djapic, Kresimir; Domislovic, Viktor; Gellineo, Lana; Rak, Benedict; Tarnovski, Lorka; Jelakovic, Bojan
Abstract : Objective: The aim of this study was to analyze the characteristics and changes in the ECG findings of adults with prehypertension (PHT) in a random sample of the general population included in the EH-UH 1 project. Design and method: Epidemiology of hypertension in Croatia 1 (EH UH-1) study is nation-wide survey on prevalence, awareness, treatment and control of hypertension (HT) in Croatia. In 2001–2003 a random sample of 1267 subjects were enrolled. Mortality data were analyzed after average period of 17 years. In this sub-analysis we included 189 untreated subjects whom GPs did an ECG. Subjects were divided into 3 groups: optimal blood pressure (OBP) < 120/80 mmHg (N = 42), PHT 120–139/80–89 mmHg (N = 78) and untreated HT (UHT) > = 140/90 mmHg (N = 69). Results: Atrial fibrillation was found in 2%, 3% and 4% in OBP, PHT and UHT group, respectively (PHT vs OBP p < 0.05). QTc interval was prolonged in 2%, 13% and 65% in OBP, PHT and UHT group, respectively (PHT vs OBP p < 0.05; UHT vs PHT p < 0.01). Tpe interval was elevated in 12%, 14% and 17% in OBP, PHT and UHT group, respectively. Left ventricular hypertrophy (Cornell) was diagnosed in 5%, 9%, and 13% in OBP, PHT and UHT group, respectively (PHT vs OBP p < 0.05; PHT vs UHT p < 0.05). Conclusions: Gradual increases in ECG changes were observed across BP groups. Even in this small cohort, we observed significantly more pathological ECG findings in the PHT group than in subjects with OBP. ECG is of utmost importance in risk stratification of subjects with PHT and helpful, simple and cheap tool in making decision how to treat PHT patient. ECG should be recorded in all subjects with PHT.